Methods and hardware oriented algorithms for making stellarator magnetic system screw-type winding images - Vorobyova, V.P.; Krugol, M.S.; Lukyanova, V.P.; Martynov, S. A.; Rudychev, Y.V.; Yurkin, A.Yu. (Вопросы атомной науки и техники, 2005)
The base methods, algorithms and standard programming tools which using for 3D images and for visualization by projection of the toroidal stellarator magnetic system screw-type winding were represented in this article. Work of the computer program for screw-type winding images manipulation and for necessary geometry information about given object receiving was represented. В статті наведено основні методи, алгоритми та стандартні програмні засоби, що використовуються для отримання 3D-зображення та зображення по проекціям гвинтових обмоток тороїдальних магнітних систем стелараторного типу. Описано роботу комп’ютерної програми, що дозволяє маніпулювати зображенням гвинтових обмоток й отримувати необхідну інформацію про геометрію об’єкту моделювання. В статье изложены основные методы, алгоритмы и стандартные программные средства, используемые для получения 3D-изображения и изображения по проекциям винтовых обмоток тороидальных магнитных систем стеллараторного типа. Описана работа компьютерной программы, позволяющей манипулировать изображением винтовых обмоток и получать необходимую информацию о геометрии моделируемого объекта.